(untitled) - LeBel, Phillip G. (Baltimore, 1982)
Energy crises and public policy, technological dimensions of energy resources, the economics of energy resources, the design and implementation of energy policy
Keywords: Energy policy,Chính sách năng lượng; Economic aspects,Khía cạnh kinh tế; United States,Hoa Kỳ